Out of Africa: The first introduced African geophilomorph centipede record from a European greenhouse (Chilopoda: Geophilidae) - Dányi, László; Tuf, Ivan Hadrián (Zootaxa, 2016)
In Europe, 184 species of Geophilomorpha are recognised (Bonato & Minelli 2014) of which eight are evaluated as alien to the region (Stoev et al. 2010, Decker et al. 2014). Four of these have been reported from greenhouses exclusively: Mecistocephalus guildingii Newport, 1843, Mecistocephalus maxillaris (Gervais, 1837), Tygarrup javanicus Attems, 1929 and Pectiniunguis pauperatus Silvestri, 1907. In this paper, we report another species, Polygonarea silvicola Lawrence, 1955, which is the first Geophilomorpha species of unambiguous African origin in Europe. Description of the specimen found in Olomouc (Czech Republic) is provided. Co-occurrence of another African species, the lithobiomorph Lamyctes africanus (Porath, 1871) (also new for Czech Republic) is also reported here.